2020
DOI: 10.1088/1757-899x/781/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Actuator Based on a Dielectric Elastomer with Quartz as a Filler for Vacuum Technology

Abstract: Modern equipment requires precise movement of objects both at atmospheric pressure and in vacuum conditions. Moreover, vacuum equipment is subjected to a number of external disturbances that adversely affect the manufacturing process and have a direct impact on the quality of manufactured products. A promising development in this area is actuators based on dielectric elastomers, characterized by a short reaction time (milliseconds) and a simple and cheap implementation. Successful implementation depends on an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The study of the filler concentration is obviously a key parameter because it allows to modulate not only the actuating properties, but also, in certain cases, the thermomechanical and/or the electrical properties of the active layer. For example, it was shown that the increase of quartz concentration in a dielectric elastomer can enhance the dielectric properties, resulting in an increased actuation amplitude [28]. Similar improvement was obtained while increasing the magnetic filler concentration in magnetic polymer composites, resulting also in the increase of the material stiffness [29].…”
Section: Introductionmentioning
confidence: 78%
“…The study of the filler concentration is obviously a key parameter because it allows to modulate not only the actuating properties, but also, in certain cases, the thermomechanical and/or the electrical properties of the active layer. For example, it was shown that the increase of quartz concentration in a dielectric elastomer can enhance the dielectric properties, resulting in an increased actuation amplitude [28]. Similar improvement was obtained while increasing the magnetic filler concentration in magnetic polymer composites, resulting also in the increase of the material stiffness [29].…”
Section: Introductionmentioning
confidence: 78%